Առնոլդ Թոյնբիի բրիտանական արտգործնախարարության «Ազգությունների խնդիրը Կովկասում» հատուկ հուշագիրը (1917 թ. հոկտեմբեր) - Նազարյան, Գևորգ
Известный историк Арнольд Тойнби является автором книги, написанной в 1915 г. об армянском геноциде («Зверства в Армении: Убийство Нации»). В том же году Тойнби начал работать в разведовательном департаменте МИДа Великобритании и во время Первой мировой войны написал целый ряд меморандумов по армянскому вопросу. В «Меморандуме о национальной проблеме на Кавказе», написанном в октябре 1917 г., автор отметил три основные национальности, проживающие в Закавказье: армяне, грузины и татары, (которые после 1930-х в советской переписи были переименованы в азербайджанцев). Тойнби представил сходства и различия между этими народами, каждый из которых имел свои сильные и слабые стороны. Меморандум был написан в то время, когда Кавказ стал стратегически важным объектом для британцев после провала на Кавказском Фронте, который защищала русская армия, это означало, что турки и немцы могут использовать эту возможность для вторжения и захвата всего кавказского региона до Каспийского моря и возможно дальше. The renowned historian Arnold J. Toynbee began his academic calling in 1915 by writing The Armenian Atrocities: The Murder of a Nation, which documented the Armenian Genocide. That same year Toynbee began working for the Intelligence Department and wrote several important Foreign Office memoranda which dealt with the Armenian Question and related subjects. One of these; The Nationality Problem in the Caucasus, was written in October of 1917 and focused on the three main nationalities of Transcaucasia: Armenians, Georgians and Tatars (who after 1930’s were officially renamed by the Soviets as Azerbaijanis). Toynbee presented similarities and differences between these three nationalities, each having a number of strengths and weakness. The memorandum was written during a time when Caucasus became an important strategic point for the British since the collapse of the Caucasus front held by the Russian army meant that the Ottoman Turks and Germans would use the opportunity to launch an invasion of the whole region and possibly move beyond the Caspian Sea.
Keywords: Պատմություն